Self-Sensing Metallic Material Based on Piezoelectric Particles - Ferreira, Pedro (2024)
Structural parts are designed to maintain their integrity, but over time factors such as aging, environmental conditions, and accidents can cause changes that lead to failure. Structural Health Monitoring (SHM) systems are essential in assessing the real condition of these parts, reducing maintenance costs, and ensuring their integrity. However, the current methods have limitations. Surface sensors are prone to damage while embedded sensors can weaken the parts. Therefore, there is a need for research in self-sensing materials for SHM applications. This study aims to address challenges in monitoring structural components throughout their lifecycle. This can be achieved by integrating advanced technology, including identifying appropriate materials and manufacturing processes, improving durability and sensitivity, and utilizing advanced techniques to characterize these materials ensuring the reliability of SHM applications. Equipping these components with monitoring technologies, data can be collected on their performance and condition, allowing for the prediction and detection of potential failures, enabling timely maintenance and repairs to be carried out. An innovative Self-Sensing Material (SSM) was developed based on piezoelectric particles embedded in metal parts (AA5058-H111) by a solid-state processing technology. Barium Titanate (BT) and Lead Zirconate Titanate (PZT) particles were introduced and dispersed into metal parts by Friction Stir Processing (FSP). Particles’ distribution and concentration were evaluated by a set of characterization techniques, demonstrating that greater concentrations, grant enhanced sensitivity to the material. The solid-state processing technology used promoted mechanical properties enhancement in the processed zone, not only by the grain size reduction but also due to the incorporation of piezoelectric particles. The SSMs generate electrical voltage when subject to strain stimulus. The sensorial properties were assessed and the response to a set of cyclic loads was measured, being coherent with the solicitations applied. Therefore, the SSM can act as a sensor and continuously monitor its integrity. Experimental result showed that SSM based on PZT particles had a sensitivity of 18.0 x 10-4 μV/MPa while based on BT particles had a sensitivity of 12.0 x 10-4 μV/MPa.